Binocular and monocular resolution thresholds throughout adulthood for luminance-modulated and contrast-modulated noise letters - Pui, Juan Woi; Sharanjeet-Kaur,; Mohd Izzuddin Hairol, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Contrast-modulated (CM) noise stimuli are thought to be processed in higher, more binocular visual areas compared to luminance-modulated (LM) stimuli, and the ability to perceive them may be more susceptible to ageing. The aim of this study was to determine monocular and binocular resolution thresholds for LM and CM noise letters throughout adulthood. Resolution thresholds for LM and CM noise letters were measured in 25 participants (age 21-70 years old) under monocular and binocular viewing. Stimuli were H, O, T and V letters created by adding or multiplying a luminance modulation function to a binary white noise carrier to create LM and CM noise letters, respectively. Resolution thresholds, determined using a 2-down-1-up staircase procedure, were lower for LM, than for CM, stimuli in both monocular and binocular viewing conditions (p<0.05). Binocular summation ratio for CM noise letters was significantly higher than that for LM noise letters (p<0.05) but declined rapidly with increasing age. For the youngest age group (20-29 years old), binocular resolution threshold was 39% better (~1.5-line improvement on the clinical letter chart) than monocular resolution threshold for CM noise letters, but only 15% better (~0.5-line improvement) when measured with LM noise letters. Binocular performance for CM noise letters declines at a faster rate with increasing age compared to that for LM noise letters. Visual function measurement with contrast-modulated stimuli might be useful to detect subtle binocular vision anomalies that may occur in early adulthood, which may be missed if measured with luminance-based stimuli alone.